Mapping and gap analysis on antimicrobial resistance surveillance systems in Kenya, Tanzania, Uganda and Zambia - Matee, Mecky (2023)
Antimicrobial resistance is a global problem and involve pathogens which have the potential to move between food producing animals and humans by direct exposure or through the food chain or the environment. The objective of this study was to determine the performance in addressing antimicrobial resistance in Kenya, Tanzania, Uganda and Zambia. Desk review and in-depth interviews were employed for data collection. Interviews were conducted with national antimicrobial resistance focal officials.